Potential uses of health promotion competencies - Shilton, T.; Howat, Peter; James, R.; Hutchins, C.; Burke, Linda (Australian Health Promotion Association, 2008)
Projects in Australia and internationally over the past two decades have sought to define and clarify competencies required to work in health promotion. It is now apparent that such competencies are very useful to health promotion practice. However, to date little attempt has been made to describe those uses.More than 200 health promotion practitioners throughout Australia were engaged in workshops to explore and define potential uses of health promotion competencies. The suggestions from these 10 workshops are summarised in eight categories of uses.Agreed health promotion competencies have potential to impact on recruitment, training, employment policy and health promotion practice.